PREPARATION OF NATIONAL PROGRAMME FOR SPENT FUEL AND RADIOACTIVE WASTE MANAGEMENT TAKING INTO ACCOUNT THE POSSIBLE FUTURE EVOLUTION OF ERDO (EUROPEAN REPOSITORY DEVELOPMENT ORGANISATION) - Tomaž Žagar; Leon Kegel (Journal of Energy Technology, 2024)
According to Council Directive 2011/70/Euratom establishing a Community framework for the responsible and safe management of spent fuel and radioactive waste (Waste Directive), each European Union member state shall ensure the implementation of its national programme for the management of spent fuel (SF) and radioactive waste (RW). On 1 February 2006, the Parliament of the Republic of Slovenia passed the Resolution on the 2006–2015 National Program for Managing Radioactive Waste and Spent Nuclear Fuel (Official Gazette of the Republic of Slovenia, No. 15/2006), which expired at the end of 2015. In March 2016, the Slovenian government adopted reviewed national programme, which sets out general activities related to SF and RW management for all radiation and nuclear facilities in Slovenia for the next ten years (2016–2025) in the fields of low‐level and high‐level waste management.  Like some other European countries, Slovenia operates a small nuclear fleet and can be expected to generate relatively small amounts of spent fuel. For such a small program, the financial and human resources required to develop a national geological disposal facility (GDF) may not be feasible or economically practical within the framework of the open and connected markets of European Union. A multinational repository that would accept spent fuel or waste packages from such countries could present a potential solution for disposal challenges. In the European Commission, this idea was recognised some years ago and was developed through two SAPIERR preparatory projects and is now being further promoted through a Working Group on the European Repository Development Organization (ERDO‐WG). This paper presents an approach how to incorporate this multinational/regional developments in the field of SF management in the national programme through a dual‐track approach.